Female Headship and Women's Work in Nepal. - Joshi Rajkarnikar, Pratistha; Ramnarain, Smita (Feminist Economics, 2020)
Literature on household headship has, by and large, tended to homogenize female-headed households (FHHs). This study presents a mixed-methods approach disaggregating the experiences of female-headed households (FHHs) in the post-conflict period in Nepal. One of four households in Nepal is estimated to be headed by a woman, either due to conflict-related male deaths (de jure, or widow heads) or men's out-migration (de facto, or wives of migrants). The study examines similarities and differences in the work responsibilities and labor market participation of de jure and de facto female heads using quantitative data from the Nepal Living Standards Survey (NLSS) and qualitative data collected through fieldwork in Nepal. While both types of households share some similar concerns, de jure and de facto female heads face different challenges in negotiating their everyday household and labor market roles. Findings inform policy interventions that can be specifically targeted toward each type of household.